(3QSGdI aj GdOdGdI Ydi GdHYK GdCNQhjs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdJUdjI GdMeO ddg GdPj Ndb GdehJ hGdMjGI djHdhce Cjce CMSf YedG hHYO CjgG GdGHf GdUGdM SCdJ Yf GdOdGdI Ydi GdHYK gd gj YbdjI Ch fbdjI hYdi XGfgG YbdjI gd Ydi LgI GdhLhH GdYbdj Ch GdLhGR GdYbdj aGYde HGQc Gddg ajce hEdjces
(3BNQgG (B:s
(3ceG GNJGQ JYGdi HYO dg ddcGaQ GdLGFR GdBNQ hgh GdfGQ hGdYPGH GdCdje fSCd Gddg GdSdGeI Hefg hcQeg hbGd GdEeGe GHf YQaI GdOdGdI Ydi GdBNQI SeYjI hdG eLGd ddYbd aj Pdc hHGddg JYGdi GdJhajbs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds